Winter snowfall can have a positive effect on photosynthetic carbon fixation and biomass accumulation of biological soil crusts from the Gurbantunggut Desert, China. Issue 2 (1st February 2016) - Zhao, Ruiming; Hui, Rong; Wang, Zengru; Liu, Lichao; Xie, Min; An, Lizhe
Abstract: Winter snowfall is an important factor in the growth and development of biological soil crusts (BSCs) in temperate desert regions of China. In this study, intact algae, lichen, and moss crusts from the Gurbantunggut Desert were collected and exposed to five experimental treatments—snow removal (0S), snow decrease to half that of ambient conditions (1/2S), ambient snow (S), snow increase to 1.5 times that of ambient conditions (3/2S), and snow increase to twice that of ambient conditions (2S)—to evaluate the effect of snowfall on the ecophysiological parameters of the BSCs during the melt and at the end of the growing period. The results clearly identified differences in physiological and ecological indexes between snowfall manipulation treatments in March, and further found that the values of most of the ecophysiological indexes were influenced by snow removal/reduction treatments, the type of BSC and their interaction effect. The chlorophyll fluorescence parameters, chlorophyll content, and the rates of photosynthesis and respiration of all three types of crust declined because of decreased soil water content with decreased snow cover, and this effect would likely be even greater under conditions of decreased precipitation. The rates of photosynthesis and respiration of the main types of BSC were changed by variations in the winter snowfall, and confirmed the existence of long‐term snowfall impacts on photosynthetic carbon fixation and biomass accumulation. These results provide a foundation for future studies to assess the potential effects of snowfall on the carbon sequestration of BSCs from arid and semi‐arid regions.